Interface engineering of nickel Hydroxide-Molybdenum diselenide nanosheet heterostructure arrays for efficient alkaline hydrogen production - Zhang, Limin; Zhang, Wenfei; Wang, Minglang; Wang, Hui; Zang, Jinhao; Shen, Weixia; Huang, Xiaowen; Kong, Dezhi; Tian, Yongtao; Xu, Tingting; Wang, Ye; Li, Xinjian (Journal of colloid and interface science, 2022)
An interconnected two-dimensional Ni(OH)2-MoSe2 nanosheet heterostructure arrays supported on carbon cloth (Ni(OH)2-MoSe2/CC) were synthezized, and further used as efficient self-supported electrocatalyst for alkaline hydrogen production. [Display omitted] •The Ni(OH)2-MoSe2 nanosheets arrays heterostructure are constructed on carbon cloth.•The Ni(OH)2 deposition time can regulate the alkaline HER activity of the catalyst.•The optimized catalyst performs a low η10 of 130 mV with a Tafel slope of 78.2 mV dec-1.•Ni(OH)2 in the catalyst promotes the water dissociation and regulates the electronic structures. The stacking of Molybdenum Diselenide (MoSe2) nanomaterials as well as its poor intrinsic conductivity lead to sluggish water dissociation kinetics, which limit the performance of the alkaline hydrogen evolution reaction (HER). Herein, we constructed Nickel Hydroxide Ni(OH)2-MoSe2 heterostructures directly on 3D self-supporting carbon cloth (CC) substrate via a simple hydrothermal and the subsequent chemical bath deposition process, then systemically studied the effect of the Ni(OH)2 deposition time on the HER performance. The synergistic effect between Ni(OH)2 and MoSe2 in the Ni(OH)2-MoSe2 heterostructures optimizes the poor conductivity and Gibbs free energy for water adsorption, thus improving the water dissociation kinetics and giving rise to fast electron transfer in the HER process. The Ni(OH)2-MoSe2/CC constructed in this way with a Ni(OH)2 deposition times of 30 min performs good catalytic activities with a low overpotential of 130 mV at -10 mA cm-2, a low Tafel slope of 78.2 mV dec-1 and good stability. Our results suggest that interface engineering combining with conductive substrate are conducive to enhance alkaline HER activity of MoSe2 and other similar transition metal dichalcogenides.